3D solid supported inter-polyelectrolyte complexes obtained by the alternate deposition of poly(diallyldimethylammonium chloride) and poly(sodium 4-styrenesulfonate) - Guzmán, Eduardo; Maestro, Armando; Llamas, Sara; Álvarez-Rodríguez, Jesús; Ortega, Francisco; Maroto-Valiente, Ángel; Rubio, Ramón G. (Beilstein Journal of Nanotechnology, 2016)
This work addresses the formation and the internal morphology of polyelectrolyte layers obtained by the layer-by-layer method. A multimodal characterization showed the absence of stratification of the films formed by the alternate deposition of poly(diallyldimethylammonium chloride) and poly(sodium 4-styrenesulfonate). Indeed the final organization might be regarded as three-dimensional solid-supported inter-polyelectrolyte films. The growth mechanism of the multilayers, followed using a quartz crystal microbalance, evidences two different growth trends, which show a dependency on the ionic strength due to its influence onto the polymer conformation. The hydration state does not modify the multilayer growth, but it contributes to the total adsorbed mass of the film. The water associated with the polyelectrolyte films leads to their swelling and plastification. The use of X-ray photoelectron spectroscopy has allowed for deeper insights on the internal structure and composition of the polyelectrolyte multilayers.
Keywords: charge compensation; hydration; polyelectrolyte multilayers; stratification; swelling